Implementasi Penilaian Afektif Pada Mata Pelajaran Pendidikan Agama Islam - Heru Wibowo; Ade Putri Muliya (Universitas Muhammadiyah Prof Dr Hamka, 2021)
This research was aimed to described how to implemented affective assessment in islamic educational subject in SMA N 1 Pariangan. This research used collecting dat technigue through interviewed method, observated and studied of documantation. In this research we knowed that implemented affective assessment of Islamic Educational subject has run well, marked by making lesson plan as well as possible and making instrumants of affective assessment to maesured behavior that would evaluate also giving appropriate score in student affective aspect evaluation in learning process. Teacher of Islamic educational subject in SMA N 1 Pariangan has begun affective assessment by making assessment lattice. Teacher used observtion paper which used for measuring spriritual behavior and social behavior of students. Affective assessment through observation did by the teacher when the students did group discussion in learning process.